Підхід до моделювання поведінкових проявів у соціальному інжинірингу в інтересах захисту інформації - Слатвінська, Валерія Микoлaївна; Слатвінська, В. М.; Василенко, Микола Дмитрович; Василенко, М. Д.; Баландіна, Наталя Миколаївна; Баландіна, Н. М.; Сисоєнко, С. В. (My University, 2020)
Стаття покликана стимулювати інтерес до особливостей підходів до моделювання поведінки людини в інформаційному середовищі та соціальному інжинірингу з метою забезпечення безпеки інформації в інформаційному кіберсередовищі. Розглянуто проблеми побудови кіль- кісної теорії людських систем. З огляду на те, що поведінка людини не піддається математичному моделюванню, жодна зі створених моделей не може бути застосована для здійснення поведінкового аналізу. Доведено потребу в новому методологічному підході до побудови моделі поведінки людини в цифровій сфері, спрямованої на захист інформації в соціальному інжинірингу. Запропоновано синергійно-криптографічний підхід до побудови моделі поведінкових проявів в умовах соціального інжинірингу та в інтересах захисту інформації.

The article is devoted to the peculiarities of approaches to modeling of human behavior in the information environment and social engineering to ensure information security in the information cyber environment. The meanings of the concepts "mathematical theory of human systems", "human activities" and "information protection" are considered. The areas of application of social engineering in the process of information protection are clarified. The attention is drawn to the existing traditional approach to ensuring the security of data storage in the information cyber environment. Furthermore, the problems of constructing a quantitative theory of human systems are considered. It is proved that since human behavior is not amenable to mathematical modeling, none of the created models can be used for behavioral analysis. Moreover, we emphasize that the authors for the first time have drawn attention to the fact that there is a need for a new methodological approach to building a model of human behavior in the digital sphere aimed at protecting information in social engineering. A synergistic and cryptographic approach to constructing a model of behavioral manifestations in the context of social engineering and information security interests is proposed. The essence of the authors' methodological approach is manifested in the fact that as a result of the synergistic interaction of "violators" (social engineers) and information owners – internet users, aimed at achieving a single goal, the possession of information that occurs under specific circumstances and at a certain time, the quality indicators of information protection methods improve. Finally, it is emphasized that to study human behavior in social engineering for further information protection, it is possible only by changing the methodological approach.
Підхід до моделювання поведінкових проявів у соціальному інжинірингу в інтересах захисту інформації / Н. М. Баландіна, М. Д. Василенко, В. М. Слатвінська, С. В. Сисоєнко // Вісник Черкаського державного технологічного університету. Серія технічні науки. - Вип. 4, 2020. - С. 57-66. DOI: 10.24025/2306-4412.4.2020.222064
Keywords: методологія; моделювання; інжиніринг; поведінка; захист інформації; methodology; modeling; engineering; behavior; information protection; Research Subject Categories::TECHNOLOGY